"Neural differences in expert guitarists during over-learned non-standard visuomotor mapping of abstract versus concrete information". (17th April 2021) - Butler, Andrew J.; James, Thomas; Pavisian, Bennis; James, Karin H.
Highlights: We exposed expert guitarists to four types of familiar visual depictions. We were able to equate motor actions while comparing the translation of vision to action across levels of abstraction. During both the perception and translation of vision to action, whole brain contrasts revealed that parietal regions were more activated for abstract stimuli and an occipito-insular circuit that was more activated for concrete stimuli. The current findings highlight that the degree of visual abstraction is an important factor modulating visual-motor processing. Abstract: Using visual information to perform actions is a fundamental aspect of human behavior. Musicians commonly translate visual information into action using both concrete and abstract visual information. We exposed expert guitarists to four types of familiar visual depictions of action instruction including musical notation (very abstract), tablature (abstract), chord diagrams (more concrete), and actual pictures of guitars chords being formed (very concrete). These were shown during fMRI scanning as the guitarists formed the appropriate chords (as visually depicted) on a magnet safe guitar fret board with strings, or where they simply viewed the visual stimuli without an action. Whole brain contrasts revealed that the right precuneus was more active for abstract instruction while an occipito-insular circuit was more active for concrete instruction. The current findings highlight that the degree of over-learned visual abstraction is an important factor modulating visual-motor processing.